Selective posterior cerebral artery amobarbital test: a predictor of memory following subtemporal selective amygdalohippocampectomy. (18th July 2019) - Catapano, Joshua S; Whiting, Alexander C; Wang, Derrick J; Hlubek, Randall J; Labib, Mohamed A; Morgan, Clinton D; Brigeman, Scott; Fredrickson, Vance L; Cavalcanti, Daniel D; Smith, Kris A; Ducruet, Andrew F; Albuquerque, Felipe C
Abstract : Background: The selective posterior cerebral artery (PCA) amobarbital test, or PCA Wada test, is used to predict memory impairment after epilepsy surgery in patients who have previously had a failed internal carotid artery (ICA) amobarbital test. Methods: Medical records from 2012 to 2018 were retrospectively reviewed for all patients with seizures who underwent a selective PCA Wada test at our institution following a failed or inconclusive ICA Wada test. Standardized neuropsychological testing was performed before and during the Wada procedure and postoperatively in patients who underwent resection. Results: Thirty-three patients underwent a selective PCA Wada test, with no complications. Twenty-six patients with medically refractory epilepsy had a seizure focus amenable to selective amygdalohippocampectomy (AHE). Six patients (23%, n=26) had a failed PCA Wada test and did not undergo selective AHE, seven (27%) declined surgical resection, leaving 13 patients who underwent subtemporal selective AHE. Hippocampal sclerosis was found in all 13 patients (100%). Twelve patients (92%) subsequently underwent formal neuropsychological testing and all were found to have stable memory. Ten patients (77%) were seizure-free (Engel Class I), with average follow-up of 13 months. Conclusion: The selective PCA Wada test is predictive of memory outcomes after subtemporal selective AHE in patients with a failed or inconclusive ICA Wada test. Furthermore, given the low risk of complications and potential benefit of seizure freedom, a selective PCA Wada test may be warranted in patients with medically intractable epilepsy who are candidates for a selective AHE and who have a prior failed or inconclusive ICA Wada test.